MIL‐53(Al) as a Versatile Platform for Ionic‐Liquid/MOF Composites to Enhance CO2 Selectivity over CH4 and N2. Issue 20 (24th July 2019) - Kavak, Safiyye; Polat, H. Mert; Kulak, Harun; Keskin, Seda; Uzun, Alper
Abstract: Five different imidazolium‐based ionic liquids (ILs) were incorporated into a metal–organic framework (MOF), MIL‐53(Al), to investigate the effect of IL incorporation on the CO2 separation performance of MIL‐53(Al). CO2, CH4, and N2 adsorption isotherms of the IL/MIL‐53(Al) composites and pristine MIL‐53(Al) were measured to evaluate the effect of the ILs on the CO2 /CH4 and CO2 /N2 selectivities of the MOF. Of the composite materials that were tested, [BMIM][PF6 ]/MIL‐53(Al) exhibited the largest increase in CO2 /CH4 selectivity, 2.8‐times higher than that of pristine MIL‐53(Al), whilst [BMIM][MeSO4 ]/MIL‐53(Al) exhibited the largest increase in CO2 /N2 selectivity, 3.3‐times higher than that of pristine MIL‐53(Al). A comparison of the CO2 separation potentials of the IL/MOF composites showed that the [BMIM][BF4 ]‐ and [BMIM][PF6 ]‐incorporated MIL‐53(Al) composites both showed enhanced CO2 /N2 and CO2 /CH4 selectivities at pressures of 1–5 bar compared to composites of CuBTC and ZIF‐8 with the same ILs. These results demonstrate that MIL‐53(Al) is a versatile platform for IL/MOF composites and could help to guide the rational design of new composites for target gas‐separation applications. Abstract : Not run of the MIL : Five ionic liquids (ILs) with different chemical and physical properties were incorporated into a metal–organic framework, MIL‐53(Al). Small anions were preferentially located near the aluminum backbone of the MOF, whereas bulky ones were preferentially located near the organic linkers. ILs with small anions increased the selectivity of the material for CO2 to up to three times that of pristine MIL‐53(Al).